Blended Learning in Higher Education: Strategic Adaptations at BIUST During the COVID-19 Pandemic - Otlhomile, Boitshoko Effort; Mokibelo, Eureka; Sebit, Sebit Mustafa (Journal of Information System and Informatics, 2025)
The study investigated the views of teaching staff members and students about the blended learning strategies that were introduced by Botswana International University of Science and Technology (BIUST) when the university transitioned from the traditional face-to-face pedagogy to blended learning during the outbreak of the Covid-19 pandemic. The findings revealed that while most teaching staff members adapted well to the use of blended learning tools, there were some challenges which including poor infrastructure, such as poor internet connectivity, limited ongoing support and unequal access to technology created difficulties for staff and students. Students valued the flexibility and autonomy that blended learning offered, but highlighted some difficulties related to limited resources and poor internet connectivity. The combination of Diffusion of Innovation theory with Social Constructivist theory provided the research with a complex framework to analyse blended learning adoption because it included both technical and social elements. The findings have important implications for higher education institutions in Botswana and comparable regions, emphasising the need to establish reliable infrastructure, inclusive resource planning, continuous capacity building, and effective communication for creating sustainable blended learning environments.